Aesthetic Rhinoplasty as a Surface-Contour Operation: From Analysis to Surgery—Personal Concepts - Pietro, Palma; Iman, Khodaei; Irina, Vasilenko (Facial Plastic Surgery, 2016)
Numerous beautiful rhinoplasty results have been created by closed rhinoplasty techniques over the past 100 years. This operation was mainly a “reduction” surgery. Overaggressive reduction rhinoplasty is not a hallmark of the closed approach per se, but represents the result of inappropriate aesthetic appraisal, inadequate technical execution, or lack of sound anatomical understanding. Clearly, an operation based primarily on reduction intrinsically exposes the surgeon to the possibility of excessive diminution of support structures and consequently undesirable side effects. The advent of the external approach in the 1970s marked a paradigm shift. In the early 1990s, the external approach witnessed further development with the introduction of “structural rhinoplasty,” a deconstruction procedure followed by structural reconstruction. Opponents of the external approach felt that opening every nose can result in an overkill, specifically because the vast majority of patients presenting for cosmetic rhinoplasty neither desire nor require major reconstruction of the nose. In the last decade, the poorly named “closed” approach, once the pariah of rhinoplasty, has been rethought especially in the light of the undesirable long-term side effects, reappraised, and found a new lease of life as “endonasal rhinoplasty.” The personal surgical evolution of the senior author (P. P.) has created the concept of “hybrid endonasal rhinoplasty” (HER), where the term “hybrid” implies the incorporation of anatomical concepts and sophisticated suturing–grafting techniques developed by “openers” into the theoretical and technical corpus of HER. The senior author (P. P.) pondered over heterogenous concepts such as filling-reshaping, derived from the so-called medical rhinoplasty, and embodied these concepts into a purely surgical endonasal perspective. Consequently, aesthetic rhinoplasty can be considered a “surface-contour” operation. Nasal analysis, preoperative work-up, surgical logic, and operative techniques have been rethought. The patient is only interested in nasal appearance, not in its anatomy, so deconstructing the nose to change the subtle and demanding interplay of light and shadow is in many cases an overkill. Our emphasis should be on those structures that can be tackled and result in the ultimate aim of altering the aesthetic aspects of surface anatomy. Surface HER can deliver on all these counts.
Keywords: rhinoplasty; closed rhinoplasty; endonasal rhinoplasty; hybrid rhinoplasty; surface-contour operation